MAKNA SIMBOLIK TRADISI ”MAPPASIKARAWA” DALAM PERNIKAHAN SUKU BUGIS DI DESA SENCALANG KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Hikmah, Samsiatul; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Mappasikarawa is one of the ceremonies or processions involved in traditional Bugis weddings in Sencalang Village, Keritang District, Indragiri Hilir Regency. In the Mappasikrawa tradition there are symbolic aspects that have certain meanings which are represented through human attributes and behavior in the Mappasikrawa tradition. The aim of this research is to analyze the meaning of symbolic situations, the meaning of social interaction products and the meaning of interpretations of the Mappasikarawa tradition in Bugis weddings in Sencalang Village.The research uses qualitative methods. The research subjects were 10 people, namely 2 Fappasikarawa, 2 Indo'Botting', 2 traditional figures, 2 parents of the bride and groom (host) and 2 brides and grooms selected using purposive techniques.The research results show that the meaning of symbolic situations in the Mappasikarawa tradition in Bugis weddings in the village includes physical objects. And social objects. The meaning of social interaction products includes the meaning of each informant. The interpreted meaning of the Mappasikarawa tradition includes open and closed actions.